Intermittent access to ethanol drinking facilitates the transition to excessive drinking after chronic intermittent ethanol vapor exposure - Kimbrough, Adam (Alcohol Clin Exp Res, 2017)
BACKGROUND: Alcohol binge drinking in humans is thought to increase the risk for alcohol use disorder. Unclear is whether drinking patterns (e.g., binge-like or stable drinking) differentially affect the transition to compulsive-like drinking in dependent individuals. We examined whether chronic binge-like drinking facilitates the transition to compulsive-like drinking in rats. METHODS: Male Wistar rats were given 5 months of intermittent access to ethanol (IAE) or continuous access to ethanol (CAE) in a two-bottle choice paradigm. Then rats were given chronic intermittent ethanol (CIE) vapor exposure. Escalation of ethanol intake and compulsive-like responding for ethanol, using a progressive-ratio schedule of reinforcement and quinine-adulterated ethanol, were measured. RESULTS: IAE rats escalated ethanol drinking after 2 weeks of two-bottle choice, whereas CAE rats exhibited stable ethanol drinking for 5 months. After 8 weeks of CIE, both IAE+CIE and CAE+CIE rats escalated their ethanol intake. However, IAE rats escalated their ethanol intake weeks sooner than CAE rats and exhibited greater ethanol intake. No differences in compulsive-like responding were found between IAE+CIE and CAE+CIE rats. However, both IAE+CIE and CAE+CIE rats showed strong compulsive-like responding compared with rats without prior IAE or CAE. CONCLUSIONS: Chronic ethanol drinking at stable or escalated levels for several months is associated with more compulsive-like responding for ethanol in rats that are exposed to CIE compared with rats without a prior history of ethanol drinking. Moreover, IAE facilitated the transition to compulsive-like responding for ethanol after CIE exposure, reflected by the escalation of ethanol intake. These results suggest that IAE may facilitate the transition to alcohol use disorder. The present study indicates that despite a moderate level of ethanol drinking, the IAE animal model is highly relevant to early stages of alcohol abuse and suggests that it may be associated with neuroadaptations that produce a faster transition to alcohol dependence.